2017
DOI: 10.1021/acscatal.7b00541
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dual Active Sites of the FeO/Pt(111) Interface and Reaction Kinetics: Density Functional Theory Study on Methanol Oxidation to Formaldehyde

Abstract: Identifying the active sites and reaction kinetics for a catalytic reaction can provide significant insight to the catalytic systems. By conducting DFT calculations, the catalytic activity of FeO/Pt(111) interfacial sites, which is an important class of catalyst with excellent activity, for methanol partial oxidation is carefully examined and compared. The O-H cleavage barrier of methanol is significantly diminished to below 0.1 eV with the aid of interfacial oxygen, which is much lower than that on the Pt(111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 65 publications
1
29
0
1
Order By: Relevance
“…Based on CATKINAS, we have completed a series of work ranging from theoretical methods development to catalyst design of different systems. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][53][54] The package aims to construct a systematic microkinetic modeling platform and our group is continuing to perfect it with more functions in the broad field of rational catalyst design, for example, automatic generation of reaction networks and interaction with first-principles calculation packages or external databases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on CATKINAS, we have completed a series of work ranging from theoretical methods development to catalyst design of different systems. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][53][54] The package aims to construct a systematic microkinetic modeling platform and our group is continuing to perfect it with more functions in the broad field of rational catalyst design, for example, automatic generation of reaction networks and interaction with first-principles calculation packages or external databases.…”
Section: Discussionmentioning
confidence: 99%
“…The reversibility iteration method (RIM) [36] is firstly developed in an F I G U R E 3 The reaction rate (A), C# coverage distribution (B), coverage summary (C), reversibility of step R1 (D) and the rate (E) and coverage prediction (F) after calculation of 5% of the points . [37][38][39][40][41][42][43][44][45][46][47][48][49][50]…”
Section: Reversibility Iteration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that the quantity of hot electrons generated in the methanol oxidation reaction is affected by the selectivity of methyl formate production using a Pt film/TiO 2 catalytic nanodiode 30 . In addition, previous studies have revealed that the partial oxidation of methanol increases when the metal-oxide interfacial sites (i.e., Pt/FeO and Au/TiO 2 ) are formed by using theoretical calculation and surface science techniques 31,32 . Therefore, the smart design of heterogeneous catalysts can improve the selectivity of metal catalysts on reducible oxide supports (e.g., Pt nanoparticles or nanowires on oxide support substrate) by engineering the metal-oxide interface 8 .…”
mentioning
confidence: 99%
“…被广泛应用于多相催化研究领域, 可以获得 分子或者晶体的几何与电子结构 [25,26] , 识别催化活性 位点 [27] , 描述反应物在催化剂表面的吸附状态 [28] , 推 断催化反应机理 [29,30] , 为传统催化剂的改性以及新型 [34,35] . 晶相结构的不确定性增加了探究催化 反应机理的难度.…”
unclassified